"Stokesley Books": John Slater Pratt and Early Victorian Publishing. (2nd January 2018) - Chase, Malcolm
ABSTRACT: The burgeoning popular market for cheap reading material in the mid-nineteenth century offered major opportunities for the print trades. Based in the Yorkshire North Riding town of Stokesley, John Slater Pratt (1807–67) transformed a country printing shop into a major producer of cheap novels and non-fiction books. He printed over 300 titles, often in several editions, most of them in the years 1841–53. Many appeared under the imprint of his own London office (1841–50), but he also printed for, and often in partnership with, a range of London and provincial publishers. This was achieved in the intensively competitive market that accompanied the industrialisation of book production and retailing, and in spite of Stokesley not being served by the railways. The firm's origins are explored, and its output analysed. Pratt's short but energetic career offers an illuminating case study both of local industrial history and entrepreneurship, and of the interplay between the English regions and the metropolis in book production, distribution and marketing.